(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study, which focuses on leaders in enterprises in Pune, examines the complex interaction between leadership styles and their effect on organisational dynamics. We examine the relationship between leaders’ perceptions of various leadership styles and their perceived impact on team dynamics and organisational outcomes through a cross-sectional survey comprising 500 top-level management professionals. Our results demonstrate a strong positive correlation between leadership styles and their perceived influence, highlighting the crucial role of leadership in determining workplace cultures. Additionally, we find a considerable correlation between leaders’ perceptions of particular leadership philosophies and their methods for making decisions, illustrating the interaction between subjective preferences and strategic considerations. Along with looking at demographic factors like gender, age, and educational attainment, the study also explores leadership involvement diversity. The implications include advice for businesses looking to promote strong leadership habits and raise productivity. This research lays the way for future studies that will broaden the geographical reach, employ qualitative methodologies, and delve into the specifics of leadership development programmes and demographic factors, while being restricted to the Pune region and depending on self-reported perceptions.